Pengalokasian Tenaga Kerja dengan Human Factor Engineering di PT. Pelindo I - Yusnawati Yusnawati; Abdul Rahim Matondang; Listiani Nurul Huda (Jurnal Optimasi Sistem Industri, 2017)
Indonesia Port Corporation I (PT Pelabuhan Indonesia I (Persero)) or PT. Pelindo I is one of the Indonesian state-owned enterprises which manages port services in western Indonesia. Shipyard unit (Unit Galangan Kapal (UGK)) is a branch of PT. Pelindo I. At present, a problem arises if more than 2 ships are being repaired at once in the unit, UGK scheduling overlaps the repairing activities. In order to solve the problem, study of human factor is important. Human factor is the study of the limitations, capabilities, and human behavior, as well as its interaction with the product, environment, equipment and the establishment of tasks and activities. One part of the human factor is the human factor in system design. In order to improve the effectiveness of the system, the human factor must be involved in each phase of the design process in the system design. This includes a number of activities to obtain input specification work, therefore the working methods and the optimal amount of labor can be determined. Human factors engineering is the application of science that utilizes research on the human factor and use the basic knowledge to design, to repair and to install the system. This research method is causal, searching for the causes which led to delays in the completion of ship repairing. Through human factor engineering approach to the allocation of labor increased by 12.23 per cent of the actual conditions, so that the delay of ship repair were not found during normal conditions.